An unofficial alliance : Scotland and Sweden 1569-1654 - Grosjean, Alexia (Northern world, 2003)
Grosjean (The Research Institute of Irish and Scottish Studies, Aberdeen) began her study to look more deeply into the few high-profile Scots who migrated to Sweden during the 17th century and became marauding mercenaries, wealthy merchants, and distinguished noblemen. She found a very different story, hidden by a confusion of national labels that.